Strategi Pengembangan Usaha Mikro Pondok Pesantren Modern Al-Kautsar Tanjungpinang - Rahman, Aulia; Hanum, Fauziah; Hantoro, Ramandha Rudwi (Yayasan Rahmat Islamiyah, 2023)
The function of Islamic boarding schools is currently having a fundamental change from educational institutions that produce cadres of scholars to institutions engaged in entrepreneurship and economic empowerment of the people. This research seeks to reveal the strategy of developing micro bussiness at the Al-Kautsar Tanjungpinang Islamic boarding school. The approach used in this study uses qualitative participatory observation. Data was collected through three different sources, key informants, observation and documentation. The results of the research data were analyzed descriptively. The results of this study indicate that Islamic boarding schools in developing micro bussiness use strategic management steps. There are four stages carried out by Islamic boarding schools in developing micro bussiness, namely: First: Islamic boarding schools carry out environmental scanning. Second: Islamic boarding schools formulate strategies in developing micro-enterprises which include optimizing resources and taking preventive steps against risks that will be accepted. Third: the next step is the implementation of the pesantren's strategies and steps that have been previously designed. Fourth: Islamic boarding schools evaluate and control the programs that have been implemented.